Digestate plus chlorella: Important alternative biotechnologies for soils and agricultural production in the context of climate change - Vozhehova Rayisa; Petrenko Svіtlana; Kholmurodova Dilafruz; Tursunova Gulmira (BIO Web of Conferences)
Over the past decade, the topic of climate change has become an integral part of our everyday life. Significant anthropogenic impact on the environment contributes to the acceleration of this process and leads to catastrophic consequences in some regions. This directs the views of scientists in many industries to the development and implementation of environmentally friendly technologies, waste-free production and the use of non-traditional approaches to the ecology of production, including agriculture. One of the areas that has recently attracted the attention of scientists from many countries around the world is the use of microalgae, among which Chlorella vulgaris is becoming increasingly popular, having a wide range of applications. The paper presents the results of the effect of a suspension culture of living cells of the microalga Chlorella vulgaris, as well as a suspension preparation of Chlorella vulgaris grown on digestate, on changes in the chemical composition of sand and on the sowing qualities of winter wheat seeds of the Shestopalovka variety. A high positive correlation was established between the length of roots and coleoptiles of winter wheat seedlings of the Shestopalovka variety (r = 0.86) in the variant with an aqueous concentration of the suspension “Chlorella with Digestat”.